Modeling of two-wheeled self-balancing robot driven by DC gearmotors - Frankovský, Peter; Dominik, L.; Gmiterko, Alexander; Virgala, Ivan; Kuryło, Piotr; Perminova, O. (Zielona Góra: Uniwersytet Zielonogórski)
This paper is aimed at modelling a two-wheeled self-balancing robot driven by the geared DC motors. A mathematical model consists of two main parts, the model of robot`s mechanical structure and the model of the actuator. Linearized equations of motion are derived and the overall model of the two-wheeled self-balancing robot is represented in state-space realization for the purpose of state feedback controller design.
Keywords: self-balancing robot; inverted pendulum; DC gearmotor; state space model